Changes in Carbon Stocks in Indian Forests : a Historical overview - Sheikh, Mehraj A.; Kumar, Munesh; Bhat, Jahangeer A.; Pala, Nazir A.; Rawat, V. R. S.; Todaria, N. P. (Indian Forester, 2012)
Reducing emissions from deforestation and degradation (REDD+) in Non-Annex-I countries is of central importance in efforts to combat climate change, because carbon management in forests will probably be the single most important st agenda of the first half of the 21st century in the context of the greenhouse effect and mitigation of global climatic changes. In this context we tried to know the position of Carbon stock in India from 1880 onwards by compiling the published literature, besides that the C stocks for the year 2003, 2005 and 2007 were also estimated on the basis of GS data published by Forest Survey of India. Carbon stocks in Indian forests from 1880 showed a marked decrease from 7940 Mt in 1880 to 3426 Mt in 1980 which have reduced to 3325.30 in 2003 to 3161.71 Mt in 2007. The carbon stock in India’s forest biomass decreases continuously despite slight increase in forest cover of the country.